ORAL DRUG DELIVERY OF INSULIN IN DIABETES MELLITUS: AN ATTRACTIVE ALTERNATE TO OVERCOME INVASIVE ROUTE - Mathur, Pooja; Mathur, Chandra Kant; Mathur, Kanchan (Universal Journal of Pharmaceutical Research, 2019)
The subcutaneous injection of insulin for the treatment of diabetes mellitus can lead to patient non-compliance, discomfort, pain and local infection is a chronic metabolic health disease affecting the homeostasis of blood sugar levels in human beings. Oral route of drug delivery system has been the most widely accepted means of drug administration other than invasive drug delivery systems. For the development of an oral insulin delivery system, we have to focus on overcoming the various gastro-intestinal barriers for insulin uptake from the gastrointestinal tract. To overcome these barriers various types of formulations such as insulin conjugates, micro/nanoparticles, liposomes, hydrogel, capsule, and tablets are designed to deliver insulin orally. Various potential ways to administer insulin orally has been explored over years but a fluctuating level of insulin release have been recorded. A number of advancement has taken place in the recent years for understanding the needs of improved oral delivery systems of insulin. This review article concentrates on the challenges for oral drug delivery of insulin as well as various carriers used for the oral drug delivery of insulin and also provides the relevant information about the clinical tested formulations of oral insulin and its patents. Peer Review History: Received 27 September 2018; Revised 5 November; Accepted 28 December; Available online 15 January 2019 Academic Editor: Dr. Marwa A. A. Fayed , University of Sadat City, Egypt, maafayed@gmail.com Reviewer(s) detail: Dr. Lucky Llegbosi Nwidu , University of Port Harcourt, Nigeria, menelucky@yahoo.com Prof. Dr. Syamsudin Abdillah , Pancasila University, Indonesia, syamsudin.abdillah@gmail.com